Safeguarding Maritime Sovereignty: Comparative Law Enforcement against Illegal Fishing in Positive and Contemporary Islamic Law - Sri Dwi Retno Ningsih; Adi Sulistiyono; Hartiwiningsih; Emmy Latifah (Faculty of Sharia, IAIN Metro, 2025)
Illegal fishing poses a critical threat to maritime sovereignty, undermining national security, ecological sustainability, and economic stability. This study conducts a comparative analysis of law enforcement against illegal fishing under Indonesian positive law and contemporary Islamic law. Employing a qualitative legal research method supported by statutory, case, and conceptual approaches, it examines the normative foundations, enforcement challenges, and philosophical principles underpinning both systems. The findings show that Indonesian positive law provides a comprehensive regulatory framework through instruments such as Law No. 45/2009 and the Fisheries Act. However, its enforcement faces significant obstacles, including jurisdictional overlaps, limited institutional resources, and weak interagency coordination. In contrast, contemporary Islamic law frames marine resource protection as part of ḥimāyah al-bi’ah (environmental protection) and maṣlaḥah (public welfare), advocating community-based accountability and ethical stewardship rooted in moral responsibility. The study highlights the potential for normative synergy between the two systems, suggesting that integrated legal pluralism could enhance maritime governance by balancing legal deterrence with ethical imperatives. Such an approach promotes not only compliance but also shared moral commitment to resource preservation. This research contributes to the discourse on environmental justice within Islamic jurisprudence and offers policy recommendations for strengthening enforcement mechanisms through a holistic, values-based legal framework.